Pelatihan Peningkatan Keamanan Data Bagi Guru di Kota Singkawang Kalimantan Barat - Saherimiko, Saherimiko; Hanum, Aliyah Nur'aini; Varanida, Dea; Alunaza, Hardi (Universitas Muhammadiyah Mataram, 2025)
Abstract: Digital transformation in education requires teachers to not only master learning technologies but also have adequate data security literacy. However, in Singkawang City, teachers' understanding of digital security remains relatively low, particularly regarding basic concepts such as phishing, malware, data encryption, and online privacy protection practices. This community service activity aims to provide teachers with an understanding of digital ethics, digital culture, and data security as part of efforts to prevent the risk of data breaches and misuse of sensitive student data. The method used in this community service activity consists of four stages: preparation, implementation of training, evaluation, and reporting. After participating in the community service activity, which involved comprehensive and practical training emphasizing practical skills, participants gained a gained a better understanding of digital ethics, digital culture, and data security. This community service activity underscores that enhancing teachers' digital security literacy not only impacts student data protection but also supports the development of a safe, ethical, and responsible digital culture within the educational environment. Abstrak: Transformasi digital dalam dunia pendidikan menuntut guru untuk tidak hanya menguasai teknologi pembelajaran, tetapi juga memiliki literasi keamanan data yang memadai. Namun, di Kota Singkawang, tingkat pemahaman guru mengenai keamanan digital masih relatif rendah, khususnya terkait konsep dasar seperti phishing, malware, enkripsi data, hingga praktik perlindungan privasi daring. Kegiatan pengabdian ini bertujuan untuk memberikan pemahaman mengenai etika digital, budaya digital, dan keamanan data bagi guru sebagai upaya mencegah risiko kebocoran dan penyalahgunaan data sensitif siswa. Metode yang digunakan dalam kegiatan pengabdian ini dengan empat tahapan, yakni persiapan, proses pelaksanaan pelatihan, evaluasi, dan pelaporan. Setelah mengikuti kegiatan pengabdian berupa pelatihan komprehensif dan aplikatif yang menekankan keterampilan praktis, peserta menjadi lebih paham dan mengerti mengenai etika digital, budaya digital, dan keamanan data. Kegiatan pengabdian ini menegaskan bahwa peningkatan literasi keamanan digital guru tidak hanya berdampak pada perlindungan data siswa, tetapi juga mendukung terbangunnya budaya digital yang aman, etis, dan bertanggung jawab di lingkungan pendidikan.